Un momento poco noto dell’analisi collettiva: M. Fagioli a Siena nell’A.A. 1974-1975 - Armando, Luigi Antonello (Il sogno della farfalla, 1993)
Un momento poco noto dell’analisi collettiva: M. Fagioli a Siena nell’A.A. 1974-1975